The complete mitochondrial genome of Undinula vulgaris (Dana, 1849) (Crustacea: Calanoida: Calanidae) - Jinwook Back; Hana Kim; Sang-Hwa Lee; Sang-Hui Lee; Myung-Hwa Shin; Byung-Jin Lim (Mitochondrial DNA. Part B. Resources, 2019)
The present study reports, for the first time, the complete mitochondrial genome (mitogenome) of Undinula vulgaris. The total mitogenome length of U. vulgaris was 15,303 bp with 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs), and 1 non-coding region. Phylogenetic analysis showed that U. vulgaris belonged to the same family. This is the second report of the complete mitogenome sequence of the family Calanidae.